Women’s Leadership in the Quran: A Critical Analysis of Contemporary Muslim Interpretation and Social Practice - Eka Ayu Sandi Pratiwi; Azilah Othman; Reni Hermila Daulay; Dinda Sahara; Zetty Rahman (Arba: Jurnal Studi Keislaman, 2026)
The debate over women’s leadership in Muslim societies reveals a tension between the normative character of the Quran, the interpretive constructions developed in a patriarchal social context, and the increasingly inclusive contemporary Muslim social practices. Previous studies have tended to separate textual analysis, interpretation, and social practices, thereby underexamining the normative-interpretive relationship among the three. This study aims to critically analyze the concept of women’s leadership in the Quran, its interpretive constructions in classical and contemporary commentaries, and the dynamics of its acceptance and negotiation in modern Muslim social practices. The study uses a qualitative approach based on a literature review, with a thematic-critical interpretive framework and a gender analysis perspective, drawing on leadership versus representative interpretive works across periods and contemporary socio-religious literature. The results show that the Quran does not establish leadership based on gender determination, but rather emphasizes the principles of competence, trustworthiness, justice, and moral responsibility as the normative foundations of leadership. The limitations on women’s leadership that emerge in some classical interpretations are primarily influenced by the epistemological framework, the structure of scholarly authority, and the patriarchal socio-historical context of the time of their interpretation. Contemporary interpretations, meanwhile, tend to reinterpret the verses on leadership with a contextual and ethical-universal approach. In contemporary Muslim social practice, the authority of interpretation is not a hegemonic one, but is negotiated through religious reinterpretation, public policy, and women’s participation in socio-political institutions. These findings confirm that the discourse on women’s leadership in Islam is dynamic and opens up a space for normative legitimacy for capacity-based leadership practices and social justice.